Analisis Sentimen Destinasi Wisata Geopark Ciletuh - Aziz, Fauzan; Thaha, Abdurrahman Rahim; Ma"ruf, Nizar Abdan (Jurnal Ilmiah Pariwisata, 2022)
West Java has a road map for 2017-2020 related to developing world-class tourist destination areas. Bandung, Cirebon, and Ciletuh and their surroundings are included in the three priority areas of tourist destinations in West Java. Ciletuh and its surrounding tourist destinations have the lowest search popularity compared to Bandung and Cirebon areas. This study aimed to determine the level of satisfaction of tourists visiting the Ciletuh area and its surroundings. This study uses sentiment analysis using the orange application with the Vader method for sentiment classification and Ekman for emotion classification. The data is taken from Google Maps and Google Reviews in English in Ciletuh and surrounding tourist destinations using web scraping techniques. The sentiment analysis results show that tourists visiting Ciletuh and its surrounding tourist destinations have a high level of satisfaction. Positive sentiment on reviews reached 77.56%, neutral sentiment 17.15%, and negative sentiment 5.29%. The emotion classification analysis was dominated by joy at 61.5%, followed by surprise, fear, sadness, anger, and disgust. Many negative sentiments and emotions are related to difficult road access to tourist attractions. This research is expected to be input for stakeholders regarding positive and negative reviews on Ciletuh tourist destinations and their surroundings. Keywords: Sentiment Analysis, Ciletuh, Review, Tourist